Pelatihan Kreativitas Anak Sekolah Minggu melalui Pengabdian kepada Masyarakat di Gereja HKBP Nommensen Pulu Brayan Medan - Bangun Munthe; Chornelyus Dehouq Simorangkir; Dini Octavia Simbolon; Ratna Sari Sitorus; Omega Yora Damanik (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This Community Service (PkM) activity was held at the HKBP Nommensen Pulu Brayan Medan Church with the aim of increasing the creativity of Sunday School children through fun and interactive educational activities. This program is motivated by the importance of developing creativity and forming children's spiritual character from an early age through a more innovative learning approach in the church environment. The method used in this activity is an experiential learning approach that involves the active participation of children in various creative activities. The program was implemented by adjusting the developmental characteristics of the participants based on their grade level. The activities carried out included a competition to name the twelve disciples of the Lord Jesus for first grade elementary school students, a competition to decorate sketches using pipettes for second grade elementary school students, and a competition to name the fruits of the Spirit for third grade elementary school students. The results of the activities showed that the Sunday School children were enthusiastic and highly participated in every activity carried out. In addition to increasing spiritual understanding, this activity was also able to develop children's creative skills, courage, and fine motor skills. This program also had a positive impact on the church community by creating a more innovative learning atmosphere and establishing good social relationships between the implementing students and the church congregation. Thus, this Community Service (PkM) activity can be an effective creative learning model to support the development of children's creativity and character in the church environment.